Research on hybrid SHEPWM based on different switching patterns - Jing, Tao; Maklakov, Alexander; Radionov, Andrey; Baskov, Sergei; Kulmukhametova, Aleksandra (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents a hybrid pulse width modulation (HPWM) strategy based on different switching patterns of selective harmonic elimination pulse width modulation (SHEPWM) for the three-level neutral point clamped (3L-NPC) converter. Specific low-order harmonics can be eliminated by SHEPWM at low switching frequency, while the remaining high-order harmonics can be selected to be simply filtered by additional hardware. Large oscillation waveform usually occurs in the transition instant between two diverse modulation situations, therefore switching between distinct switching patterns can be problematic if no effective means is taken, especially when the effect of smooth and fast transition at any time is considerable. A universal and valid control strategy, which maintains the high-quality output voltage and current, is proposed and implemented in this paper to address this issue. Simulation results obtained from MATLAB/SIMULINK are presented to analyze the performance and validate the feasibility and effectiveness of this control scheme.